“It’s Not Going to Be Okay”: Stoic Wisdom for a Difficult World - Davis, Trent (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2024)
This paper opens with a family anecdote in which my future mother in-law, when asked what wise advice she would offer undergraduate university students, replied, “I would tell them it’s not going to be okay.” Can we learn to keep engaging with the world despite its inevitable disappointments? I propose that Stoic philosophy, by “orienting” our “attention” and “courage,” can help us navigate the troubled post-COVID world we share. To help make this more concrete, I describe a critical moment I observed in which a maskless shopper insulted fellow patrons in a grocery store for wearing a mask. I then develop the Stoic themes of acknowledgement (a commitment to the facts) and affinity (reaching out to others to build community). In the conclusion I return to the “maskless shopper” incident to consider how my two Stoic themes might help open a dialogue with this person. After discussing the limitations to such an undertaking, given the surge in populism over the last decade, I conclude with the appropriately tough-minded Stoic proposition that despite the obstacles, we must keep trying.